Acidification of prehydrolysis liquor and spent liquor of neutral sulfite semichemical pulping process. (October 2016) - Fatehi, Pedram; Gao, Weijiue; Sun, Yonghui; Dashtban, Mehdi
Highlights: The existence of LCC compounds was provided in PHL and NSSC spent liquors. Acidification was a means for isolating lignin/lignosulfonate from spent liquors. The heating values of precipitates were related to the properties of precipitates. Precipitates of PHL can be used as fuel due to their low ash content. Abstract: Acidification has been commercialized for producing kraft lignin from black liquor of kraft pulping process. This work intended to evaluate the effectiveness of acidification in extracting lignocelluloses from the spent liquor of neutral sulfite semichemical pulping (NSSC) process and from prehydrolysis liquor (PHL) of kraft-based dissolving pulp production process. The results showed that the NSSC and PHL spent liquors had some lignin-carbohydrate complexes (LCC), and that the square weighted counts of particles with a chord length of 50–150 μm in the spent liquors were significantly increased as pH dropped to 1.5. Interestingly, the acidification reduced the lignosulfonate/lignin content of NSSC and PHL by 13% or 20%, while dropped their oligosugars content by 75% and 38%, respectively. On a dry basis, the precipitates had more carbon, hydrogen and a high heating value of 18–22 MJ/kg, but less oxygen, than spent liquors. The precipitates of PHL could be used as fuel.